Multi-trait multi environment analysis for stability in MABC lines of Chickpea (Cicer arietinum) - JORBEN, J; RAO, APOORVA; BHARADWAJ, C; NITESH, S D; TIWARI, NEHA; KUMAR, TAPAN; SAXENA, D R; YASIN, M; SONTAKKE, P L; JAHAGIRDAR, JAGDISH E; HEGDE, V S (The Indian Journal of Agricultural Sciences, 2022)
Fusarium wilt (Fusarium oxysporum f. sp. ciceris) is a major disease that can cause up to 90% yield loss in Chickpea (Cicer arietinum L.). The presence of 8 physiological races of Foc (0, 1A, 1B/C, 2, 3, 4, 5 and 6) makes it a complex task in the development of disease-resistant cultivar. Thus, Pyramiding of Foc races 1, 2, 3, 4 and 5 was undertaken using WR 315 as donor and Pusa 372 as recurrent parent through Marker assisted backcross (MABC) breeding approach. A total of 20 genotypes, including 17 MABC derived lines of Pusa 372 × WR 315, susceptible parent (Pusa 372), resistant check (WR 315) and national check (JG 16) were used. Multi-location testing of advanced MABC lines at 4 different regions (Amla, Badnapur, Sehore, IARI-New Delhi) was carried out using randomised block design (RBD) in two replications during 2020–21 winter (rabi) season. Usually, multi environment testing is performed involving a single trait, which provides lower reliability in selection of lines, compared to multi-trait analysis. The present study identifies highly stable Fusarium wilt resistant lines with higher yield advantage using MTSI (Multi trait stability index) and GGE (Genotype main effect and genotype × environment interaction) biplot methodology. From GGE biplot analyses the PC1 explains 84.97% and PC2 explains 8.96% of variability. MTSI results revealed that genotype (G) 1, 4 and 3 were stable for the multiple characters studied. But, based on GGE-mean stability value G 11, 12 and 3 were identified for higher yield and better stability values. Based on MTSI and GGE, G 3 may be considered as a stable line for multiple traits including yield superiority.